2007
DOI: 10.1080/02713680701531090
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Topical Travoprost and Unoprostone on Optic Nerve Head Circulation in Normal Rabbits

Abstract: Topical travoprost or unoprostone significantly increased the ONH blood velocity with a single instillation and the effect persisted for 24 hr after a 7-day instillation. The effects of these drugs against retinal and ONH circulation are probably associated with the production of endogenous prostaglandins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 34 publications
2
8
1
Order By: Relevance
“…Interestingly, formulation of this drug with two different preservatives showed disparate results, and more studies are needed to confirm the effect of this drug on RI. Other research groups have shown that travoprost is effective for improving blood flow, as found in the present study with travoprost BAK (25)(26)(27) . Further, in the present research, travoprost with BAK as a preservative significantly decreased RI, while travoprost with POLYQUAD did not; therefore, the preservative BAK may have some effect in this instance.…”
supporting
confidence: 79%
“…Interestingly, formulation of this drug with two different preservatives showed disparate results, and more studies are needed to confirm the effect of this drug on RI. Other research groups have shown that travoprost is effective for improving blood flow, as found in the present study with travoprost BAK (25)(26)(27) . Further, in the present research, travoprost with BAK as a preservative significantly decreased RI, while travoprost with POLYQUAD did not; therefore, the preservative BAK may have some effect in this instance.…”
supporting
confidence: 79%
“…; Ohashi et al. ; Sugiyama et al. ) as well as a direct neuroprotective effect on neuronal cell death (Melamed ; Mukuno et al.…”
Section: Discussionmentioning
confidence: 99%
“…Latanoprost increases the optic nerve head blood flow in humans, 4,5 and travoprost increases the ocular blood flow in both humans and animals. 6,7 In addition, we reported that the PG analogues latanoprost, isopropyl unoprostone, and tafluprost induce concentration-dependent relaxation of isolated rabbit ciliary arteries. [8][9][10] Using laser speckle flowmetry, we reported that tafluprost, latanoprost, and travoprost prevent the endothelin-1 (ET-1)-induced decrease of optic nerve head ocular blood flow in rabbits.…”
Section: Introductionmentioning
confidence: 99%